2014
DOI: 10.1111/jpi.12181
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Arabidopsis serotonin N‐acetyltransferase and its role with caffeic acid O‐methyltransferase in the biosynthesis of melatonin in vitro despite their different subcellular localizations

Abstract: Serotonin N-acetyltransferase (SNAT) is the penultimate enzyme in melatonin biosynthesis. We cloned SNAT from Arabidopsis thaliana (AtSNAT) and functionally characterized this enzyme for the first time from dicotyledonous plants. Similar to rice SNAT, AtSNAT was found to localize to chloroplasts with peak enzyme activity at 45 °C (Km , 309 μm; Vmax , 1400 pmol/min/mg protein). AtSNAT also catalyzed 5-methoxytryptamine (5-MT) into melatonin with high catalytic activity (Km , 51 μm; Vmax , 5300 pmol/min/mg prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 40 publications
5
126
0
Order By: Relevance
“…Dual expression of SNAT and COMT in E. coli resulted in the production of both Nacetylserotonin and melatonin, which promotes beneficial biological activities in animals and plants (Sompol et al 2011;Lee et al 2014b). Several highly relevant differences in the melatonin biosynthetic genes between animals and plants were identified through comparisons with the melatonin synthetic capacity in the heterologous E. coli system.…”
Section: Discussionmentioning
confidence: 99%
“…Dual expression of SNAT and COMT in E. coli resulted in the production of both Nacetylserotonin and melatonin, which promotes beneficial biological activities in animals and plants (Sompol et al 2011;Lee et al 2014b). Several highly relevant differences in the melatonin biosynthetic genes between animals and plants were identified through comparisons with the melatonin synthetic capacity in the heterologous E. coli system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a caffeic acid O-methyltransferase (COMT) was found to convert Nacetylserotonin to MEL in plants 32,37,41 . This suggests that alternate routes and enzymes may be involved in this process.…”
Section: Biosynthesismentioning
confidence: 99%
“…TDC in plants and SNAT in animals are generally considered to be the rate limiting steps in these pathways. For example transgenic studies in rice have found that up-regulation of TDC can increase endogenous 5HT and MEL Downloaded by [University of Leeds] at 08:27 04 October 2015 7concentrations; however limited literature has also suggested that ASMT may be a more important in determining the amount of melatonin produced in some plant species 34,39,40 .Recently, a caffeic acid O-methyltransferase (COMT) was found to convert Nacetylserotonin to MEL in plants 32,37,41 . This suggests that alternate routes and enzymes may be involved in this process.…”
mentioning
confidence: 98%
“…A concomitant increase in the precursor 5-hydroxyguaiacyl units and a decrease in the S/G ratio are also frequently observed. Interestingly, a recent study implied that AtOMT methylates N-acetylserotonin into melatonin possessing N-acetylserotonin O-methyltransferase (ASMT) activity [15], results that were also evaluated and identified in rice [16]. Melatonin is implicated in pleiotropic functions during plants growth and development [17].…”
Section: Introductionmentioning
confidence: 99%